Pemanfaatan LMS Moodle dalam Pembelajaran Berbasis TPACK untuk Meningkatkan Kemampuan Analisis Peserta Didik Pada Materi Sistem Saraf - Nurdiani, Nia; Tari Tauhida; Cartono; Saiman Rosamsi (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2024)
Analytical ability is the ability of students to describe a problem in learning material, in other words, students are able to know, understand, and apply what the teacher has conveyed. One way to improve students' analytical skills is to apply a learning process based on the TPACK framework. This study aims to determine the effectiveness of learning with the e-learning method using the LMS Moodle as a component of the TPACK framework, on the subject matter of the Nervous System. This study used a pre-experimental method with a one-group pretest - posttest design. The instrument used to measure the knowledge ability of students is in the form of pretest and posttest questions as many as 20 items. The subjects used were 23 students in class XI MIPA A SMA Angkasa Lanud Husein Sastranegara Bandung. The results showed that the average pretest score was 56.7 with the lowest score being 20 and the highest score being 85, with the posttest average score being 84.6, the lowest score being 40 and the highest score being 100, and the results of the N-Gain test. obtained a score of 0.66 with low improvement criteria, while from the acquisition of student questionnaires it was found that learning using the e-learning method that uses LMS Moodle as a component of the TPACK framework is categorized as very attractive to students. Thus, it can be concluded that there is an increase in students' analytical skills on the concept of the Nervous System material by utilizing the LMS Moodle in TPACK based learning.